The use of endoscope in maxillo-facial trauma. - Fernandes, Victor Santos; Ramos, Nuno; Matias, Júlio; Andrade, Miguel; Fraga, Z Biscaia (Acta Médica Portuguesa, 2004)
The authors discuss the endoscopic techniques as an adjunctive in the evaluation and treatment of maxillo-facial fractures, particularly in the mandible, with special attention to the reduction and osteosynthesis near the condyle for those fractures with clear surgical indication. And also as a support in to the correct execution of the transbuccal techniques for treatment of body and angle fractures and in the repair of the orbital floor. The perspective of this work is the systematic search for quality, with diminution of iatrogenic effects and surgical risk, aims of modern surgery, even if with some technical difficulties and consumption of extra time, efforts.